Advances in biological therapies for dyslipidemias and atherosclerosis - Valanti, E. K.; Dalakoura-Karagkouni, K.; Siasos, G.; Kardassis, D.; Eliopoulos, A. G.; Sanoudou, D. (MetabolismMetabolismMetabolism, 2021)
Atherosclerosis is a multifactorial disease influenced by genetics, lifestyle and environmental factors. Despite therapeutic advances that reduce the risk of cardiovascular events, atherosclerosis-related diseases remain the leading cause of mortality worldwide. Precise targeting of genes involved in lipoprotein metabolism is an emerging approach for atherosclerosis prevention and treatment. This article focuses on the latest developments, clinical potential and current challenges of monoclonal antibodies, vaccines and genome/transcriptome modification strategies, including antisense oligonucleotides, genome/base editing and gene therapy. Multiple lipid lowering biological therapies have already been approved by the FDA with impressive results to date, while many more promising targets are being pursued in clinical trials or pre-clinical animal models.
Valanti, Eftaxia-KonstantinaDalakoura-Karagkouni, KaterinaSiasos, GerasimosKardassis, DimitrisEliopoulos, Aristides GSanoudou, DespinaengResearch Support, Non-U.S. Gov'tReview2020/12/09 06:00Metabolism. 2021 Mar;116:154461. doi: 10.1016/j.metabol.2020.154461. Epub 2020 Dec 5.
Keywords: Animals; Atherosclerosis/epidemiology/*therapy; Biological Therapy/methods/*trends; Dyslipidemias/epidemiology/*therapy; Endocrinology/methods/trends; Humans; Therapies, Investigational/methods/trends